The Russian-Ukrainian War and the future of world order - Ashcallay Samaniego, Samuel (2023)
The war between Russia and Ukraine takes place in a world order in decline with a wide diffusion of power in the system, in which the main motivation of international actors seems to be competition. It is a period of transition, characterized by the breakdown of global governance institutions and of the principles of economic openness, security cooperation, and democratic solidarity. This paper attempts to elucidate how the Russia-Ukraine war, along with other dynamics operating in the international context for two decades, could influence the configuration of a new world order; what characteristics should this new order need; and what must be the role of each actor in it. Based on the analysis of the causes of the conflict, it is proposed the need to define a new, more benign order that recognizes the different institutional and political configurations in the system, as well as to maintain the necessary conditions to address the main global challenges, promote economic prosperity, and minimize the risks of major war.